An Expedited Transition to the Back Wall Suturing for Side-to-Side In Situ Microvascular Anastomosis: A Technique Update. Issue 6 (6th August 2020) - Ravina, Kristine; Fredrickson, Vance L; Donoho, Daniel A; Cavaleri, Jonathon M; Strickland, Ben A; Lam, Jordan; Russin, Jonathan J
Abstract: BACKGROUND: The side-to-side in situ microvascular anastomosis is an important tool in the cerebrovascular neurosurgeon's armamentarium. The execution of the side-to-side anastomosis, however, can be limited by the inability to acquire sufficient visualization and approximation of the recipient and donor vessels. OBJECTIVE: To expedite the transition to the back wall suturing of the donor and recipient vessels during side-to-side in situ microvascular anastomosis. METHODS: Incorporation of the first suture throw from the outside to the inside of the vessel lumen with the initial stay suture at the proximal apex of the arteriotomy is described. The apical knot is tied between one limb of the resultant loop and the free end of the suture. The remainder of side-to-side anastomosis can then be completed in a standard fashion starting from the inside of the lumen. RESULTS: This modification allows for an expedited transition to the back wall suturing of the 2 arterial segments and avoids difficulties associated with taking the first bite from behind the knot at the proximal apex of the arteriotomy or the transfer of the needle between the approximated vessels. This updated technique is illustrated with a case example, illustration, and video. CONCLUSION: This technical modification for the side-to-side anastomosis helps optimize microsurgical efficiency by limiting needle, suture, and vessel handling after the initial suture placement, which has classically been a challenge of this bypass.